Решите пожалуйста 1,3,4, задания, по желанию можете решить 2

Решите пожалуйста 1,3,4, задания, по желанию можете решить 2
Гость
Ответ(ы) на вопрос:
Гость
№1 [latex]\frac{tg \alpha }{1 - tg^{2} \alpha} * \frac{ctg^{2} \alpha - 1}{ctg \alpha} = \frac{tg \alpha * tg \alpha * (ctg^{2} \alpha -1) }{1-tg^{2} \alpha} = \frac{tg^{2} \alpha * (ctg^{2} \alpha -1) }{1 - tg ^{2} \alpha } = \frac{1 - tg^{2} \alpha }{1 - tg^{2} \alpha } = 1[/latex] №2 - А [latex]\frac{sin( \frac{\pi}{4} + \alpha ) - cos( \frac{\pi}{4} + \alpha ) }{sin( \frac{\pi}{4} + \alpha ) + cos( \frac{\pi}{4} + \alpha ) } = \frac{sin\frac{ \pi }{4} * cos \alpha + cos\frac{ \pi }{4} * sin \alpha - cos\frac{ \pi }{4} * cos \alpha + sin \frac{ \pi }{4} * sin \alpha }{sin\frac{ \pi }{4} * cos \alpha + cos\frac{ \pi }{4} * sin \alpha + cos\frac{ \pi }{4} * cos \alpha - sin \frac{ \pi }{4} * sin \alpha } = [/latex] [latex] \frac{ \frac{ \sqrt{2} }{2} * cos \alpha + \frac{ \sqrt{2} }{2} * sin \alpha - \frac{ \sqrt{2} }{2} * cos \alpha + \frac{ \sqrt{2} }{2} * sin \alpha }{ \frac{ \sqrt{2} }{2} * cos \alpha + \frac{ \sqrt{2} }{2} * sin \alpha + \frac{ \sqrt{2} }{2} * cos \alpha - \frac{ \sqrt{2} }{2} * sin \alpha} = \frac{ \frac{ \sqrt{2} }{2} * sin \alpha + \frac{ \sqrt{2} }{2} * sin \alpha }{ \frac{ \sqrt{2} }{2} * cos \alpha + \frac{ \sqrt{2} }{2}* cos \alpha } =tg\alpha [/latex] №2 - Б [latex]\frac{1 - cos( \frac{3 \pi }{2} - \beta ) + cos (6 \pi - \beta )}{1+sin( \beta + 8 \pi ) - sin ( \frac{3 \pi }{2} + \beta )} = \frac{1 + sin \beta + cos \beta }{1 + sin \beta + cos \beta } = 1[/latex] №3 [latex]sin^{3} (- \frac{9 \pi }{4} ) + cos^{2} (- \frac{5 \pi }{2}) = ( - \frac{ \sqrt{2} }{2} )^{3} + 0 = - \frac{( \sqrt{2})^{3} }{8} = - \frac{ \sqrt{2} }{4} [/latex] №4 [latex]cos( \frac{7 \pi }{2} + \alpha) * tg( \frac{ \pi }{2} - \alpha )- sin( \frac{ \pi }{2} - \alpha ) + ctg ( \frac{3 \pi }{2} - \alpha ) = tg \alpha \\ sin \alpha * ctg \alpha - cos \alpha +tg \alpha = tg \alpha \\ sin \alpha * \frac{cos \alpha }{sin \alpha } - cos \alpha + tg \alpha = tg \alpha \\ cos \alpha - cos \alpha + tg \alpha = tg \alpha [/latex] [latex] \\ tg \alpha = tg \alpha [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы